El Proyecto de Investigación Arqueológica Huacramarca. Resultados preliminares - Vega Centeno, Rafael (2008)
The results of the Huacramarca Archaeological Research Project field seasons are presented. These results have allowed defining the extent and internal organization of a Late Intermediate Period settlement of the southern side of the Yanamayo basin. Excavations have provided significant contexts that will allow reconstructing different activities that took place in the residential structures that characterized Huacramarca. In addition, survey results reveal an extensive occupation of the Huacramarca Mountain, with several smaller settlements and funerary structures spread throughout the mountain slopes. Finally, research results have been complemented with preservation and restoration procedures that have allowed the enhancement of the monument.